2022
DOI: 10.24083/apjhm.v17i1.1131
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Four-Visit ANC in Indonesia: A population-based study

Abstract: Introduction: The number of maternal, neonatal and child mortality remains high in developing countries, including Indonesia. Antenatal care (ANC) coverage is an indicator of health-care use and access during pregnancy. Receiving at least four visits of ANC increases the chances of receiving appropriate maternal health interventions as one of the tracer indicators for universal health coverage in the Global Strategy for Women's, Children's, and Adolescents' Health Monitoring Framework (SDG indicator 3.8.1). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
1
Order By: Relevance
“…Our results contrast the earlier study that found better conditions in the urban area 30–32. The improvement may be due to better economic development, namely better mothers’ education and working opportunities 33. It is worth mentioning that there has been an improvement in the utilization of maternal services though it is yet to be optimal.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results contrast the earlier study that found better conditions in the urban area 30–32. The improvement may be due to better economic development, namely better mothers’ education and working opportunities 33. It is worth mentioning that there has been an improvement in the utilization of maternal services though it is yet to be optimal.…”
Section: Discussioncontrasting
confidence: 99%
“…[30][31][32] The improvement may be due to better economic development, namely better mothers' education and working opportunities. 33 It is worth mentioning that there has been an improvement in the utilization of maternal services though it is yet to be optimal. Owning health insurance, called Jampersal, is mandatory for everyone in Indonesia since 1 January 2014.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the further analysis of the recent National Family Health Survey, India [13,17]. The further analysis of 2016 DHS in Nepal and 2017 DHS, Indonesia also has similar findings [12,18]. The women using internet had higher odds of receiving four or more ANC visits in this study.…”
Section: Ancsupporting
confidence: 89%
“…A study reported that maternal near-miss rates were 59.6 per 1000 person-years for pregnant women with ANC contact, compared to 86.1 per 1000 person-years for those without ANC contact (Kebede et al, 2021 ). Similarly, previous studies have shown that pregnant women who did not receive ANC had 1.3-3.9 times higher odds of neonatal death compared to those who had at least four ANC contacts (Andriani et al, 2022 ; Arunda et al, 2017 ). Thus, adequate ANC contact is essential to reduce the risk of maternal and infant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 59%